NHT Type Cooperative Learning Model (Numbered Heads Together) On Student Learning Results in Indonesian Language Learning in The Third Grade of SDN 1 Kawalimukti - Indriyanti, Indriyanti; Hakam, Kama Abdul (International Conference on Elementary Education, 2021)
This research is motivated by the low achievement outcomes from the third-grade students in Indonesian subjects. This can be seen from the preliminary research data on student learning outcomes in Indonesian subjects only 45% of the students reached the KKM. The NHT (Numbered Heads Together) type cooperative learning model is expected to provide solutions to improve student learning outcomes in Indonesian subjects for the third grade of elementary school. The purpose of this study is to describe the practical implementation of the cooperative learning model NHT and to describe the improvement of the student learning outcomes in Indonesian subjects. The research method used Classroom Action Research (CAR) by adapting the Kemmis & Mc. Model. Taggart in two research cycles and each cycle consisting of planning, implementing, observing/observing, and reflecting. The results showed that there was a positive influence on students thus their learning outcomes increased. These results can be seen from the increase in each cycle, namely the average student learning outcomes in cycle I was 74.6% and increased by 9.6 points in cycle II to 84.2%. Then, the percentage of completeness according to the KKM in cycle I was 72% increased by 28 points in cycle II becoming 100%. Based on the research results above, it can be concluded that the application of the cooperative learning model NHT type (Numbered Heads Together) can gave a positive influence on student learning outcomes in Indonesian subjects for the third grade in Public Elementary School 1 Kawalimukti in Kawali District, Kawalimukti Sub-District, Ciamis.